Developing assessment in improving students' digital literacy skills - Amnie, Erlida; Rosidin, Undang; Herlina, Kartini; Abdurrahman, Abdurrahman (Graduate School, Universitas Negeri Yogyakarta, 2021)
This research aims to develop an assessment of problem-solving skills in improving students' digital literacy skills. This research is directed to produce physics learning assessments that can improve students' digital literacy using problem-solving skills assessments. The use of assessments that refer to the problem-solving skills stage is expected to improve students' digital literacy. The study is an R D research with the Borg and Gall development model. On the preliminary research, a questionnaire is needed to detect need analysis of an assessment that can help improving student digital literacy skills. Questionnaires were used to collect expert review data, while cognitive tests were used to collect data on students' problem-solving skills. Cognitive tests by posttest form were held to find out the progress of students understanding during the learning process using the products. The results of content validity by Aiken’s V is 0.80. The factor analysis is seen by the Bartlett test value with Chi-squares = 1.604 and significance at 0.659. Therefore, the problem-solving skills assessment from the aspect of content and construction has valid criteria and is suitable for use. The N-Gain test results of students problem-solving skills in the experimental class by 0.3 with a quite effective category higher than the control class of 0.12 with a quite effective category. The results show that the use of assessment of problem-solving skills effectively improved students digital literacy skills.